Carbamazepine versus levetiracetam in epilepsy due to neurocysticercosis. (22nd October 2020) - Santhosh, Akhil P.; Kumar Goyal, Manoj; Modi, Manish; Kharbanda, Parampreet S.; Ahuja, Chirag K.; Tandyala, Naresh; Prabhat, Nandita; Singh, Rajveer; Mehta, Sahil; Vinay Mahesh, Karthik
Abstract : Background: The choice of antiepileptic drug (AED) in newly diagnosed neurocysticercosis (NCC) patients with epilepsy continues to be arbitrary. We compared efficacy and side effect profile of levetiracetam (LEV) and carbamazepine (CBZ) for the treatment of seizures in newly diagnosed patients with NCC. Patients and methods: This was an open‐labeled randomized comparative monotherapy study including newly diagnosed drug naïve patients of NCC (n = 99) presenting with seizures who were randomized in 1:1 ratio using computed generated numbers. All patients were followed up for at least six months after start of treatment. The primary outcome measure was seizure control over six months following start of AEDs. Results: Fifteen (15.2%) patients [CBZ‐ 4(8.2%); LEV‐ 11(22%)] developed recurrence of seizures. A trend ( p  = 0.09) was found toward better control of seizures in CBZ compared to LEV. Two (4%) patients in LEV group and 17 (34.6%) patients in CBZ group developed drug‐related minor side effects ( p  < 0.0001). Three patients in CBZ group needed discontinuation of therapy due to skin rash. Eleven patients who relapsed while on LEV did not have any recurrence of seizures after switching over to CBZ. Out of 3 patients who relapsed while receiving CBZ and were changed to LEV, two developed seizures during follow‐up. Conclusion: CBZ and LEV could be used as alternatives in newly diagnosed patients of NCC at the behest of minor side effects in the CBZ group.